Metamaterials: Tailorable Zero‐Phase Delay of Subwavelength Particles toward Miniaturized Wave Manipulation Devices (Adv. Mater. 40/2015). (21st October 2015) - Zhao, Qian; Xiao, Zongqi; Zhang, Fuli; Ma, Junming; Qiao, Ming; Meng, Yonggang; Lan, Chuwen; Li, Bo; Zhou, Ji; Zhang, Peng; Shen, Nian‐Hai; Koschny, Thomas; et al.
<x xml:space="preserve">Abstract</x> Adjustable zero phase delay and equiphase‐control are demonstrated by Q. Zhao and co‐workers in single and multilayer dielectric particle arrays with high index and low loss. As shown on page 6187, the polarization‐independent near‐zero permeability is the origin of the wave‐control near the first Mie magnetic resonance. The proposed design paves the way for subwavelength devices and opens up new avenues for miniaturization and integration of terahertz and optical components.